Corporate Governance - Turner, Catherine (Elsevier, 2011)
his book will provide a user-friendly guide to current and emerging issues in corporate governance, especially for accountants and directors. The book explains terminology used in a jargon free way, and sets out to give you a practical guide to establishing a robust, yet workable governance framework for your enterprise.